Glucocorticoid-induced adrenal insufficiency after receiving intravenous methylprednisolone for Graves' ophthalmopathy: a case report - Yanne Pradwi Efendi; Dinda Aprilia; Eva Decroli (Universa Medicina, 2026)
BACKGROUNDGraves’ ophthalmopathy (GO) is the most common extrathyroidal manifestation of Graves’ disease and can significantly impair visual function and quality of life. High-dose intravenous methylprednisolone (IVMP) is recommended as first-line therapy for moderate-to-severe active GO due to its superior efficacy and tolerability compared with oral glucocorticoids. However, IVMP therapy may be associated with rare but potentially serious adverse effects, including suppression of the hypothalamic–pituitary–adrenal (HPA) axis leading to GI adrenal insufficiency (GI-AI). Case descriptionWe report the case of a 38-year-old man with Graves’ disease who developed AI following IVMP therapy for moderate-to-severe GO. The patient received five weekly doses of IVMP 500 mg (cumulative dose 2.5 g) for progressive ocular symptoms. He subsequently presented with fatigue, weight gain, moon face, and buffalo hump. Laboratory evaluation revealed a markedly low morning serum cortisol level of 1 mcg/dL, confirming adrenal insufficiency. Patient was diagnosed with GI-AI accompanied by features of iatrogenic Cushing’s syndrome. Management consisted of hydrocortisone replacement therapy at a dose of 20 mg/day along with ongoing antithyroid treatment using methimazole. Serial monitoring of cortisol levels demonstrated gradual recovery of HPA axis function, accompanied by clinical improvement. ConclusionThis case highlights that glucocorticoid-induced adrenal insufficiency can occur on IVMP used for GO. Clinicians should maintain a high index of suspicion and perform appropriate adrenal function monitoring during and after IVMP therapy to ensure early detection and safe management of this potentially life-threatening complication.